VALUE CHAIN ANALYSIS OF COW'S MILK AT CIBUBUR GARDEN DAIRY (CIBUGARY) DAIRY FARM, CIPAYUNG, EAST JAKARTA - Zulmanery Manir; Rizki Adi Puspita Sari; Fida Yunia Rosanti (Syarif Hidayatullah State Islamic University Jakarta, 2021)
Post-milking cow's milk or in the form of fresh unprocessed cow's milk has very vulnerable properties caused by the surrounding environment, such as air, temperature, and bacteria so that it can cause the company to suffer losses, so it is necessary to carry out proper processing and packaging. This study aims to map the supply chain of cow's milk in Cibugary Farm. Analyze the cow's milk value chain at Cibugary Farm. Analyze the added value of cow's milk in each member of the supply chain. Determine the distribution margins to business actors along the production value chain, and determine the priority of dairy products that can be developed at the processing level.The qualitative analysis describes descriptively the supply chain, value plan, process flow, and overview of Cibugary Livestock. Meanwhile, quantitative analysis is used to analyze the added value in animal husbandry, processing, and marketing as well as exponential comparison methods.The results of this study are that the members of the cow's milk supply chain consist of Cibugary-farms, cow milk processing industries, resellers, Cibugary outlets, and consumers. The value chain condition of cow's milk processing at Cibugary Farm is quite good in terms of the availability of infrastructure, raw materials, and market access, but the ability of competent human resources, in terms of the technology used is still relatively simple. The biggest profit obtained by cow's milk value chain actors is at the Cibugary dairy farm level of Rp. 65,396,062.83 /month. The amount of margin obtained in pasteurized milk processing is Rp. 35,000, yogurt processing industry is Rp. 45,000, mozzarella cheese processing industry is Rp. 85,000, a reseller is Rp. 3,000. The results of the calculation of the exponential comparison method can be concluded that the most potential processed product is Pasteurized Milk, with a value of 76,881,381.